Understanding and managing cardiovascular outcomes in liver transplant recipients - Izzy, Manhal (Curr Opin Organ Transplant, 2019)
PURPOSE OF REVIEW: Cardiovascular disease (CVD) is a common cause of mortality after liver transplantation. The transplant community is focused on improving long-term survival. Understanding the prevalence of CVD in liver transplant recipients, precipitating factors as well as prevention and management strategies is essential to achieving this goal. RECENT FINDINGS: CVD is the leading cause of death within the first year after transplant. Arrhythmia and heart failure are the most often cardiovascular morbidities in the first year after transplant which could be related to pretransplant diastolic dysfunction. Pretransplant diastolic dysfunction is reflective of presence of cirrhotic cardiomyopathy which is not as harmless as it was thought. Multiple cardiovascular risk prediction models have become available to aid management in liver transplant recipients. SUMMARY: A comprehensive prevention and treatment strategy is critical to minimize cardiovascular morbidity and mortality after liver transplant. Weight management and metabolic syndrome control are cornerstones to any prevention and management strategy. Bariatric surgery is an underutilized tool in liver transplant recipients. Awareness of ‘metabolic-friendly’ immunosuppressive regimens should be sought. Strict adherence to the cardiology and endocrine society guidelines with regard to managing metabolic derangements post liver transplantation is instrumental for CVD prevention until transplant specific recommendations can be made.